The impact of generative AI on creative and structural academic writing: Enhancing originality, compliance, and autonomy in English language learning - Galuh Dwi Ajeng; Febriyantina Istiara; Aksendro Maximilian; Tommy Hastomo; Andri Wicaksono (JEELS (Journal of English Education and Linguistics Studies), 2026)
The integration of Generative Artificial Intelligence (GenAI) in English as a Foreign Language (EFL) writing instruction has transformed how students develop both creative and academic writing skills. However, its widespread use raises concerns about overreliance, which may affect students’ autonomy and critical thinking. This study investigates: (1) the impact of GenAI on creative writing quality, particularly originality, cognitive flexibility, and expressive innovation; (2) its role in enhancing structural academic writing, including coherence, organization, and grammatical accuracy; and (3) students’ perceptions of autonomy and dependence in AI-assisted writing. Using a mixed-methods sequential explanatory design, the study involved 80 undergraduate students divided into experimental and control groups. Quantitative data were analyzed using independent-samples t-tests and MANOVA, while qualitative data were examined through thematic analysis. The findings indicate that GenAI significantly improves both creative and structural writing performance while fostering learner autonomy, although risks of emerging dependency remain. Overall, this study highlights the importance of a balanced and pedagogically guided integration of GenAI to enhance writing quality while sustaining students’ creativity, autonomy, and critical thinking.